Sorafenib paradoxically activates the RAS/RAF/ERK pathway in polyclonal human NK cells during expansion and thereby enhances effector functions in a dose- and time-dependent manner - Lohmeyer, J.; Nerreter, Thomas; Dotterweich, J.; Einsele, H.; Seggewiss-Bernhardt, R. (Clinical and Experimental Immunology, 2018)
Natural killer (NK) cells play a major role in host immunity against leukaemia and lymphoma. However, clinical trials applying NK cells have not been as efficient as hoped for. Patients treated with rapidly accelerated fibrosarcoma (RAF) inhibitors exhibit increased tumour infiltration by immune cells, suggesting that a combination of RAF inhibitors with immunotherapy might be beneficial. As mitogen-activated protein kinases (MAPKs) such as raf-1 proto-oncogene, serine/threonine kinase (CRAF) regulate NK cell functions, we performed an in-vitro investigation on the potential of clinically relevant short-acting tyrosine kinase inhibitors (TKIs) as potential adjuvants for NK cell therapy: NK cells from healthy human blood donors were thus treated with sorafenib, sunitinib or the pan-RAF inhibitor ZM336372 during ex-vivo expansion. Functional outcomes assessed after washout of the drugs included cytokine production, degranulation, cytotoxicity, apoptosis induction and signal transduction with/without target cell contact. Paradoxically, sorafenib enhanced NK cell effector functions in a time- and dose-dependent manner by raising the steady-state activation level. Of note, this did not lead to NK cell exhaustion, but enhanced activity against target cells such as K562 or Daudis mediated via the RAS/RAF/extracellular-regulated kinase (ERK) pathway, but not via protein kinase B (AKT). Our data will pave the path to develop a rationale for the considered use of RAF inhibitors such as sorafenib for pre-activation in NK cell-based adoptive immune therapy.
CRIS-Team Scopus Importer:2023-03-23
Keywords: immunotherapy; NK cells; tyrosine kinase inhibitor; ZM336372